LEGAL CONSEQUENCES OF COOPERATION BETWEEN NOTARY PARTNERS AND BANKS ON THE VALIDITY OF THE DEEDS MADE - Afrian, Robiatul (Authentica, 2024)
Notaries, in their efforts to get clients to offer cooperation, become partners with banks in the execution of authentic instruments. The problem arises in relation to the cooperation between notary partners and banks, which is contrary to the Notary Code of Ethics, since it is stated that notaries may not cooperate with offices/services/legal entities which, in principle, act as intermediaries in order to find and/or obtain clients. The formulation of this research problem is: (1) What are the legal consequences of the partnership agreement between a notary and a bank? (2) What is the validity of the notarial deed made as a result of the partnership with the bank? By using normative legal research methods, using a legislative approach and a conceptual approach, as well as the research specifications used, namely perspective analysis, namely describing and analyzing facts through laws and regulations. It can be concluded that the cooperation between the notary and the bank is contrary to the Code of Ethics and the UUJN, but does not affect the validity of the deed that will be made by the notary, because basically the agreement of the parties is the one that gives birth to an agreement and the notary is only the registrar of the deed, not intervening that affects the content of the deed..